West Kalimantan Folktales : Supplementary Material for Teaching Narrative Text - Yuni Susanti; Sudarsono Sudarsono; Yohanes Gatot Sutapa Yuliana (IKIP PGRI Pontianak, 2023)
The purpose of the current study was to describe the use of folktales and evaluate whether folktales are feasible to teach narrative text. This study focuses on West Kalimantan folktales as supplementary material teaching narrative texts encountered in scholarly articles. The researcher used a Systematic Literature Review method. The data for this study were gathered from three academic papers connected to the West Kalimantan folktales. The findings of this study indicate that West Kalimantan folktales may be used as supplemental material for enhancing the narrative text.